Complications and long-term outcome of primary obstructive megaureter in childhood - Gimpel, Charlotte; Masioniene, Liuda; Djakovic, Nenad; Schenk, Jens-Peter; Haberkorn, Uwe; Tönshoff, Burkhard; Schaefer, Franz (Pediatric nephrology, 2010)
We assessed the clinical outcome of 49 children with 56 primary obstructive megaureters (POM) treated with the primarily conservative approach recommended by the 2001 German consensus guidelines. POM occurred more often in boys (71%) and on the left side (67%). Forty-three POM (77%) were treated conservatively. Four kidneys underwent immediate surgery and nine of 52 kidneys managed primarily conservatively worsened subsequently, requiring surgery. Urinary tract infections (UTI) were the most common complication (mean 1.3 per patient), with frequent hospital admission (45%). During the first year of life, the incidence of UTIs was 55% less during prophylactic antibiotic treatment (0.94 vs.0.42 UTIs per year, p < 0.05). Spontaneous regression occurred in 80% of POMs with dilated non-obstructive renogram, but in <20% with intermediate or relevant obstruction. All megaureters with <8.5 mm sonographic diameter regressed, but none over 15 mm. Eight patients had a poor outcome (partial kidney function <40% (n = 6), renal atrophy (n = 3)), but in seven of the patients, these findings were already present postnatally. In summary, the long-term outcome of POM appears favorable with mainly conservative treatment. UTI as the most common complication was 55% lower with antibiotic prophylaxis in infants. Adverse outcome was more closely related to congenital kidney hypoplasia than to degree of obstruction.